The circus scare - Keene, Carolyn (Keene, Carolyn. Nancy Drew and the clue crew, 2007)
Nancy Drew and the Clue Crew investigate when circus acts are sabotaged. When the circus comes to River Heights, Nancy and the Clue Crew investigate who is stealing some very important props from the performers.